Ways of attracting foreign direct investment in the Ukrainian economy - Yuliia Horodnichenko (Hryhorii Skovoroda University in Pereiaslav, 2021)
Subject of research is the directions and ways of attracting foreign direct investment in Ukraine. The purpose of the article is to study the essence and features of foreign direct investment and to study the foreign experience of ways to attract direct investment to Ukraine. Methods used in the research process: method of system-structural analysis and synthesis, method of comparative analysis, generalization, general scientific, special methods of scientific knowledge and other research methods. Study results. The importance of foreign investments in the activity and development of the state is described. The main measures that need to be implemented to attract foreign investment are identified. International investment cooperation, given the high level of its efficiency, provides the country and its businesses with a number of current and future benefits. Positive and negative factors influencing the attraction of foreign investments into the state economy are outlined. One of the most common ways to attract direct investment to Ukraine is to create joint ventures, which are manifested in the processes of cooperation, pooling of knowledge, efforts, resources and experience. Motivational levers of influence on direct investment partners are singled out. They can be divided into two large groups. In the first case, firms are mainly engaged in the sale of goods and services produced in other countries, in the second - invest in the creation of production facilities in this country in order to sell products in the local market or export it to markets in other countries. Application of results. The results of the study can be used in the activities of the Ministry of Finance of Ukraine, the Verkhovna Rada of Ukraine, the National Commission on Securities and Stock Market, as well as in higher education institutions in the teaching of economic disciplines. Conclusions. Foreign investment plays an important role in the development of the country's economy. Attracting funds from foreign investors contributes to the intensification of the investment process, the introduction of new technologies, the use of advanced foreign experience, the development of small and medium-sized businesses, the growth of investment potential of the territories.